Underwriter incentives and IPO pricing - Espenlaub, Susanne; Mohamed, Abdulkadir; Saadouni, Brahim (Journal of Corporate Finance, 2024)
We examine the impact of incentive fees paid to IPO underwriters at issuers' discretion on IPO pricing and short-term performance. We expect that better-incentivized underwriters produce more information required for IPO pricing reducing underwriters' reliance on investors' information production which requires compensation through IPO underpricing. Using a novel dataset, we find that incentive compensation mitigates the partial-adjustment phenomenon. IPOs with stronger incentives have more informative price ranges, higher price revisions, longer road shows and lower initial returns largely due to interaction effects between underwriters' incentives and their information-production capabilities. Using a battery of tests and addressing endogeneity, our results remain robust.